Medication Safety and Risk Reduction: Collaborative Roles of Pharmacy, Public Health, and Nursing - Khalid Yahya Mohammed Almagadi; Abdullah Mushabib Salman Jalaad; Mansour Saeed Mohammed Alqahtani; Saeed Saad Saeed Al Toman; Ali Mohammed Ahmd Al Ben Essa; Ali Mohammed Alalkami; Ali Ahmed Mohammed Falqe; Abdulaziz Defayr Alasiri; Debsa Aiyd Alqahtani; Abdullah Ahmed Abdullah Naji (International Journal of Medical Toxicology and Legal Medicine, 2024)
Safety medication is cardinal in health care since medication errors might be associated with considerable side effects on the patients. The problem is multilevel because it will require incorporating various disciplines like pharmacy, public health, and nursing in seeking novelty methods of enhancing medication safety and reducing some of the medication-related risks. Pharmacy, public health, and nursing professionals can work toward designing a safer active medication use system based on their distinctive expertise in approaches such as multidisciplinary communication, technology adoption, engaging the patients, policy development, and continuous quality improvement. The bottom line from the article is that all parties need to pledge on matters involving the safety of the patients, while further collaboration shall be called for to overcome various emerging challenges and ultimately improve health outcomes.